Simulation–adventure virtual worlds in the metaverse for engineering education and training: A domain-stratified narrative review - Fortuna, Aprilla; Raihan, Muhammad; Saputra, Dimas Aulia; García, Juan Luis Cabanillas; Ayasrah, Firas Tayseer (Researcher and Lecturer Society, 2025)
This study employs a narrative review methodology to analyze the integration of Virtual Worlds, specifically Simulation Worlds and Adventure Worlds, in engineering education, aiming to enhance conceptual understanding, technical competence, and 21st-century skills. The study synthesizes 23 peer-reviewed articles selected from the Scopus database using stringent inclusion criteria. Simulation-based learning models focus on procedural accuracy and conceptual mastery, while adventure-based models emphasize transversal skills like creativity, collaboration, and problem-solving. Hybrid models combining both approaches are identified as the most effective, fostering technical expertise and soft skills simultaneously. Despite challenges such as high infrastructure costs and potential cognitive overload, immersive virtual environments offer significant opportunities for scalable and adaptable remote learning. Thematic analysis is employed to synthesize findings and provide recommendations for future implementation. This review highlights the importance of integrating these technologies in engineering education and suggests exploring their long-term impact on engineering careers. Additionally, it underscores the need for further research on the application of immersive technologies across diverse engineering disciplines, focusing on overcoming existing challenges and maximizing their educational potential.